Analisis Pengukuran Kinerja Koperasi (Studi Kasus Pada “KOPEGTEL PALAPA” Mataram) - Hendra Tauhid; Tati Atmayanti (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
Cooperatives are one business entity based on family principles. This study aims to determine the Performance of Kopegtel "Palapa" Mataram if it is measured in accordance with the Cooperative Rating Guidelines (Kep. Men. No. 06 / Per / M. KUKM / III / 2008). This type of research is descriptive with a quantitative case study approach at Kopegtel Palapa Mataram. Data collection techniques with interview methods, documentation and questionnaire method (questionnaire) population amounted to 166 respondents and a sample of 50 respondents based on the results of sampling with slovin formula. The variables measured include: (1) Aspects of active business entities; (2) aspects of business performance that are increasingly healthy; (3) cohesiveness and participation of members; (4) Orientation aspects to member services; (5) Service aspects to the community; (6) Aspects of contribution to development. Data analysis is based on the Kep Cooperative Rating Guidelines. Men. No. 06 / Per / M. KUKM / III / 2008. The results of Kopegtel Palapa's analysis get a total score of 343 where the score ranges from above 340 to 419, so in 2017 Kopegtel Palapa's performance is in the category of "Quality" or "Good" .